A new ornithopod (Dinosauria, Ornithischia) from the Upper Cretaceous of Antarctica and its palaeobiogeographical implications - Rozadilla, Sebastian; Agnolin, Federico; Novas, Fernando Emilio; Aranciaga Rolando, Alexis Mauro; Motta, Matias Javier; Lirio, Juan Manuel; Isasi, Marcelo Pablo (Cretaceous Research)
A new ornithopod dinosaur from the Upper Cretaceous (Maastrichtian) Snow Hill Island Formation, at James Ross Island, Antarctica is here described. This new taxon, named as Morrosaurus antarcticus gen. et sp. nov., is represented by a fragmentary right hind limb belonging to a medium-sized individual. Our phylogenetic analysis nests the new taxon in a monophyletic clade of Southern Hemisphere ornithopods that includes most Patagonian and Antarctic ornithopods. Several members of this group share a slender and bunched foot with narrow metatarsal IV, expanded chevrons, and bowed humerus without deltopectoral crest. Several features indicate that these ornithopods exhibit adaptations for a specialized cursorial mode of life. The recognition of Patagonian and Antarctic Ornithopoda belonging to a monophyletic clade reinforces palaeobiogeographical signals indicating that Patagonia, Antarctica and Australia shared a common Late Cretaceous terrestrial fauna. Fil: Rozadilla, Sebastian. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Agnolin, Federico. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina. Universidad Maimónides; Argentina Fil: Novas, Fernando Emilio. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Aranciaga Rolando, Alexis Mauro. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Motta, Matias Javier. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo ...